1992
DOI: 10.1002/nt.2620010109
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecene synergism, additivity, and antagonism: The significance of the maximally quiescent ratio

Abstract: The interactive effect of the combinations of trichothecene mycotoxins often found in fungus infected plants, contaminated grain, and other biological systems is poorly understood. Growth inhibition of the yeast Kluyveromyces marxianus was used to measure the effects of HT-2 toxin, roridin A, and T-2 toxin as individual toxins or as binary mixtures. A value, the combination index, was derived which indicates the interactive effects of a binary mixture of toxins. The interaction is affected by the ratio of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…The interactive effect of DON and NIV found in the present study was in agreement with some previous in vitro studies on yeast growth (Madhyastha et al, 1994) and on DNA syntheses in L929 cells (Tajima et al, 2002), although some reported additivity of trichothecenes (Thuvander et al, 1999). A plausible explanation for such discrepancies could be differences in the ratios of trichothecenes in the mixture, or to differences in effect levels (Jones et al, 1995;Koshinsky and Khachatourians, 1992). The possible interaction between ZEA and FB1 was not fully elucidated in the current stage.…”
Section: Combinations % Reduction In Cell Viabilitysupporting
confidence: 77%
“…The interactive effect of DON and NIV found in the present study was in agreement with some previous in vitro studies on yeast growth (Madhyastha et al, 1994) and on DNA syntheses in L929 cells (Tajima et al, 2002), although some reported additivity of trichothecenes (Thuvander et al, 1999). A plausible explanation for such discrepancies could be differences in the ratios of trichothecenes in the mixture, or to differences in effect levels (Jones et al, 1995;Koshinsky and Khachatourians, 1992). The possible interaction between ZEA and FB1 was not fully elucidated in the current stage.…”
Section: Combinations % Reduction In Cell Viabilitysupporting
confidence: 77%
“…In in vitro studies testing the effect of multiple trichothecene exposure on fungi, there was evidence of interactive relationships between different toxins [47]. This is an important consideration, since F. graminearum, a strongly aggressive species against cereals, is capable of producing NIV, fusaranon-X, DON, 3-acetyldeoxynivalenol (3-ADON), as well as ZEA, depending on geographic location [33,48].…”
Section: Introductionmentioning
confidence: 99%
“…Moulds on the floor can extend through continuity to the concrete feeding areas and thus come in contact with the combined fodder from pigs' alimentation. According to Koshinsky and Khachatourians (1992) the presence of fungi that produce toxins in animal food or the accommodating areas does not automatically imply toxicity. When more fungi are present, each of them can produce different mycotoxins and this combination can cause more adverse effects in comparison to only one mycotoxin because of the additive or synergic interaction.…”
Section: Resultsmentioning
confidence: 99%